Banking on a standard IFX for the retail and commercial banking arenas. - Haehn, Mike
One of the basic challenges of XML developers is formulating best practices and design guides for defining their XML content. This is especially pervasive in industry communities, which is why there has been a growth of community based XML specifications and standards.